Atypical Chest Pain: An Unusual Presentation of Spinal Metastasis due to Penile Carcinoma. (26th June 2016) - Pywell, Sarah; Hasan, Shumaila; Sohail, Mohammad Zain; Mamarelis, Georgios; Dott, Cameron; Khan, Mohammad Taimur; Sivanadarajah, Naveethan
Abstract : Spinal metastases may present in a myriad of ways, most commonly back pain with or without neurology. We report an unusual presentation of isolated atypical chest pain preceding metastatic cord compression, secondary to penile carcinoma. Spinal metastasis from penile carcinoma is rare with few cases reported. This unusual presentation highlights the need for a heightened level of clinical suspicion for spinal metastases as a possible cause for chest pain in any patients with a history of carcinoma. The case is discussed with reference to the literature.